Covalent Grafting Terbium Complex to Alginate Hydrogels and Their Application in Fe3+ and pH Sensing. Issue 2 (13th November 2018) - Zhang, Zeyu; Liu, Fengyi; Xu, Quanqing; Zhu, Han; Zhu, Aixin; Kou, Junfeng
Abstract: Biocompatible luminescent hydrogels containing covalently linked terbium complexes with a macrocyclic ligand are prepared by a facile method. The environmentally friendly preparation procedure is carried out at room temperature using water as a solvent. These new hybrid materials can act as luminescent sensors to detect Fe 3+ with relative selectivity and high sensitivity. The hydrogels also show pH sensing with a wide range. Abstract : Alginate hydrogels containing covalently linked terbium complexes are prepared by a facile method. These luminescent hydrogels can be used as sensors to detect Fe 3+ ions and pH.